1979
DOI: 10.1111/j.1151-2916.1979.tb19077.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Enthalpies of the TiO2 Polymorphs

Abstract: The enthalpies of transformation of pure, well‐characterized samples of brookite and anatase to rutile were determined by solution calorimetry in a 3Na2O·4MoO3 melt at 971 ±2 K. The experiments gave the following results: brookite→rutile, ΔH°971= ‐0.17±0.09 kcal mol−1; anatase → rutile, ΔH°971= ‐0.78±0.20 kcal mol−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 8 publications
4
74
0
2
Order By: Relevance
“…7), rutile is more stable than anatase. This has been confirmed by thermodynamic studies [5,9,76,148,152], which show that negative pressures would be required for anatase to be more stable than rutile [2]. The transformation to rutile thus is irreversible.…”
Section: Stability Of the Tio 2 Phasessupporting
confidence: 58%
See 1 more Smart Citation
“…7), rutile is more stable than anatase. This has been confirmed by thermodynamic studies [5,9,76,148,152], which show that negative pressures would be required for anatase to be more stable than rutile [2]. The transformation to rutile thus is irreversible.…”
Section: Stability Of the Tio 2 Phasessupporting
confidence: 58%
“…Since rutile is the equilibrium phase [2,7,9,20,76,113,148,152], the presence of anatase demonstrates that these studies cannot represent equilibrium conditions, which normally employ phase diagrams for illustration. Dachille et al [154] reported what was considered to be an pressure-temperature diagram approximating equilibrium for TiO 2 , which is shown in Fig.…”
Section: Stability Of the Tio 2 Phasesmentioning
confidence: 99%
“…Abbreviations defined in Table 1. for the system MgO-CO2-H20 Hemingway and Robie, 1973) clearly show the stable phase assemblage to be brucite + magnesite + H20(1) rather than hydromagnesite, nesquehonite, or artinite, yet the latter minerals are widespread and the former assemblage is unknown in surface rocks so far as we can ascertain. Similarly, anatase is a TiO: polymorph commonly found in diagenetic, hydrothermal, and altered rocks, yet it is clearly metastable relative to rutile (Jamieson and Olinger, 1969;Mitsuhashi and Kleppa, 1979;Robinson et al, 1982). In addition, Jiang et al (1990) presented evidence that illite (and smectite) are metastable relative to micas + pyrophyllite for all geological conditions.…”
Section: Metastability Of Boehmite Gibbsite Bayerite and Nordstranmentioning
confidence: 99%
“…[6][7][8][9][10] However, the enthalpy change of the anatase to rutile transformation remains somewhat controversial, with room-temperature experiments yielding values ranging from ⌬H 298 ϭϪ11.7 kJ/mol ͑Ref. 7͒ to ϩ0.42 kJ/mol ͑Ref.…”
Section: Introductionmentioning
confidence: 99%